Glacier Flow and Topography Measurements with TerraSAR-X and TanDEM-X - Eineder, Michael; Abdel Jaber, Wael; Floricioiu, Dana; Rott, Helmut; Yague-Martinez, Nestor (2011 IEEE International Geoscience and Remote Sensing Symposium, 2011)
We report on results from spaceborne velocity and topography measurements of the Drygalski glacier, Antarctic Peninsula. For our analysis we use a time series of TerraSAR-X data acquired between 2007 and 2010 which enables us to perform an error analysis and to determine higher order velocity parameters such as acceleration. Our estimated accuracy for velocity estimation is on the order of 2 cm/day and we find a weak slow down at the terminus of the glacier. Very first TanDEM-X single pass interferometric data sets acquired in 2010 allow us to reconstruct the 3D-glacier topography with unprecedented accuracy, delivering both, surface topography and roughness.